2020
DOI: 10.1093/rb/rbaa014
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of small intestine submucosa in tissue engineering

Abstract: With the development of tissue engineering, the required biomaterials need to have the ability to promote cell adhesion and proliferation in vitro and in vivo. Especially, surface modification of the scaffold material has a great influence on biocompatibility and functionality of materials. The small intestine submucosa (SIS) is an extracellular matrix isolated from the submucosal layer of porcine jejunum, which has good tissue mechanical properties and regenerative activity, and is suitable for cell adhesion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 110 publications
1
38
0
Order By: Relevance
“…With preserved bioactive factors and growth factors, SIS has gained much attention in tissue engineering and subsequent clinical applications as a highly supportive scaffold ( Fig. 7 ) [ 62 ]. More recently, in vivo research on the application of porcine SIS in the treatment of IUAs demonstrated that SIS can change the receptive factors (higher expressions of uteroglobin and HOXA10) and significantly increase endometrial thickness and reduce the percentage of fibrotic areas in IUA rat modes [ 63 ].…”
Section: Postoperative Adjuvant Therapy Methodsmentioning
confidence: 99%
“…With preserved bioactive factors and growth factors, SIS has gained much attention in tissue engineering and subsequent clinical applications as a highly supportive scaffold ( Fig. 7 ) [ 62 ]. More recently, in vivo research on the application of porcine SIS in the treatment of IUAs demonstrated that SIS can change the receptive factors (higher expressions of uteroglobin and HOXA10) and significantly increase endometrial thickness and reduce the percentage of fibrotic areas in IUA rat modes [ 63 ].…”
Section: Postoperative Adjuvant Therapy Methodsmentioning
confidence: 99%
“…Recently, the use of small intestine submucosa (SIS) has been also proposed for the production of large and small TEVGs [ 183 ]. Typically, SIS can be derived either from the porcine or ovine origin [ 184 ].…”
Section: Decellularized Vascular Graftsmentioning
confidence: 99%
“…Besides nanopatterning, micropatterning is also a unique tool for fundamental studies of interactions between cells and materials [45][46][47][48][49][50][51][52][53][54]. In particular, cells were found to adhere on adhesive microislands only over a critical size [55,56].…”
Section: Introductionmentioning
confidence: 99%